Development of Potential Culinary and Shopping Tourism in Central Java Province - Fafurida Fafurida; Shanty Oktavilia; Karsinah Karsinah; Syiva Fauziah (Muhammadiyah University Press, 2020)
Central Java is a province that has more tourist attractions, but from the number of tourist visit, it only has relatively small. Therefore, it requires a development strategy of tourism sector. One of the tourism potential that can be developed is culinary and shopping tourism. The purpose of this research are identifying the potential of culinary and shopping tourism in Central Java and formulating the strategy to develop the tourism potential. The analysis tools used are statistic descriptive, Geographic Information System and SWOT analysis. The findings from this research are the potential of culinary tourism in Central Java in very potential category can be found in seven regencies/cities. The development strategy of culinary tourism is featuring the taste of Central Java, developing the culinary central area that gives multiplier effect on the society, repairing and adding facilities supporting the tourism. The potential of shopping tourism in very potential category can be found in six regencies/ cities. The development strategy of shopping tourism is conducted by making innovation and utilizing the existing tourism potential, joining in some events, holding bazaar that supports the development of shopping tourism, and completing the directions and the map of shopping tourism potential to facilitate the tourists.